Do board educational background, occupational background and ownership structure matter for directors' remuneration disclosure? Some Malaysian evidence - Esa E.; Zahari A.R. (IGI Global, 2023)
Following the Asian economic tumult 1997, most of the researchers in Malaysian have been focusing on the issues of disclosure, transparency and boardroom failures. The crisis had led to statements about corporate governance in times of financial crisis and the lessons that can be learnt. A lot of prior literature examined the factors influencing the aspects of disclosure without giving reference to the educational and occupational background of the board of directors and the ownership structure, which influence the decision-making regarding director remuneration disclosure. Thus, the objective of this study is to investigate how the educational and occupational background of the board of directors and ownership structure affect director remuneration disclosure in Malaysian public listed companies. Very limited research has been explored in the issue of directors' remuneration disclosure. The director remuneration checklist is used to measure the director remuneration disclosure among Malaysian public listed companies. The findings of this study revealed that ownership structure is significantly associated with the extent of directors' remuneration disclosure, while the board's educational and occupational background are found to not be associated with the extent of directors' remuneration disclosure. 2016 by IGI Global. All rights reserved.